MicroRNA-20a-5p Ameliorates Non-alcoholic Fatty Liver Disease via Inhibiting the Expression of CD36 - Wang, Xin; Ma, Yan; Yang, Long-Yan; Zhao, Dong (Frontiers in Cell and Developmental Biology, 2020)
Fatty acid translocase CD36 (CD36) plays an important role in the initiation and pathogenesis of chronic liver disease and non-alcoholic fatty liver disease (NAFLD). The purpose of this study is to investigate the regulation of microRNA-20a-5p (miR-20a-5p) on CD36 in the pathogenesis of NAFLD. Human plasma samples were obtained from NAFLD patients and healthy controls. Mice fed with high fat diet to induce an in vivo NAFLD model. Histology staining was performed to examine the morphology and lipid deposition of mice liver tissue. Real-time PCR, Dual-luciferase assay, and western blotting were employed to detect the relationship between miR-20a-5p and CD36. The expression level of miR-20a-5p was decreased in NAFLD patients, HFD mice, and free fatty acid (FFA)-treated HepG2 cells or primary mouse hepatocytes, accompanied by increased lipid production in hepatocytes. MiR-20a-5p suppressed the expression of CD36 to reduce lipid accumulation via binding to its 3’-untranslated region (UTR). However, under the condition of interference with CD36, further inhibition of miR-20a-5p would not cause lipid over-accumulation. In this study, we found that miR-20a-5p played a protective role in lipid metabolic disorders of NAFLD by targeting CD36, which indicated the prospect of miR-20a-5p as a biomarker and treatment target for NAFLD.